Analisis Perbandingan Program Aplikasi Berbasis Acces Point Dengan Program Aplikasi Dari Lazismu Universitas Muhammadiyah Surakarta (UMS) - Zulfa, Anik Puji Lestari, Dr. Agung Riyardi, M.Si, Dr. Muhtarom, S.H, M.H (2017)
ABSTRACT The purpose of this research is to know about diversification between zakat application base acces point with application base excel and to know about efficiency level of the application by used primary data from the result of interview by LAZISMU management. The data will be analysis used deskriptifapproachmentmethod, it is to describe the condition or phenomenon with a words or sentences to get the conclusion. According the result of research, zakat application based excel in LAZISMU UMS used autodebit by cutting the saleries of muzakki and directly enter to LAZISMU UMS account. According to the informant, muzakki only from lecture and staff UMS. It can be included that the zakat application based-excel which used by LAZISMU UMS as for as efficient. Keywords : Efficiency, zakat application, LAZISMU UMS.